DOES INCENTIVES AND SUPERVISION HAVE IMPACT ON PERFORMANCE EMPLOYEES FOR SOUTH LAMPUNG REGENCY TRANSPORTATION SERVICE - Asyri Muminatin; M Oktavianur; Hendri Dunan; Defrizal (Program Studi Magister Manajemen, 2023)
The purpose of this study was to find out whether there is an influence of incentives and leadership supervision on employee performance at the South Lampung Regency Transportation Service. This study uses qualitative analysis methods and uses explanatory research types. The population in this study were all employees of the South Lampung Regency Transportation Service and the sample used was 51 people and then analyzed descriptively and inferentially. The results showed that incentives had a positive and significant effect on employee performance. Furthermore, leadership supervision also had a positive and significant effect on employee performance and the hypothesis test showed that incentives and leadership supervision had a positive and significant effect on performance. Based on the conclusions, there are results obtained in this study, including, on the incentive variable, the incentive component that gets the lowest score is